Mediating effects of psychological capital on the influencing relationship between social isolation and anxiety symptoms of maintenance hemodialysis patients - Li, Ying; Yang, Fan; Zhang, Jianhua; Xiang, Meng; Wu, Haibo (Frontiers in Psychology, 2025)
BackgroundLimited research has examined the direct or indirect effects of social isolation on anxiety symptoms. This study investigated the mediating effect of psychological capital (PsyCap) on social isolation and anxiety symptoms.MethodsThe study included 202 maintenance hemodialysis (MHD) patients from Shanghai Hospital in China. Data collection utilized basic data, social isolation, anxiety self-assessment, and psychological capital questionnaires. Statistical analysis employed PROCESS4.1 and SPSS26.0 for univariate and correlation analyses, with Model 4 being utilized for mediation effect assessment.ResultsSmoking history, heart failure, and dialysis time were identified as significant factors associated with anxiety in MHD patients. Social isolation score is positively correlated with PsyCap (r = 0.442, p < 0.001), and negative correlated with anxiety symptoms (r = −0.786, p < 0.001). The mediating effect of PsyCap accounts for 7.693% of the total effect.ConclusionPsychological capital plays a partial mediating role in the relationship between social isolation and anxiety in MHD patients. It is necessary to strengthen the assessment of social isolation in MHD patients to improve PsyCap and reduce the risk of anxiety symptoms.